SOCIAL CAPITAL IN EMPOWERING WOMEN FARMER GROUPS IN DUSUN SUMURJURANG KELURAHAN SUMURREJO SEMARANG CITY - Silvia Theresani Allawiyah; Thriwaty Arsal; Hamdan Tri Atmaja (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study investigates the role of social capital in empowering Women Farmer Groups (KWT) in Dusun Sumurjurang, KelurahanSumurrejo, Semarang. Using a qualitative phenomenological approach, the research examines three components of social capital: social networks, trust, and social norms, as theorized by Robert D. Putnam. Data were collected through in-depth interviews, field observations, and documentation from the KWT